Willingness of volunteers from Canadian Blood Service's Stem Cell Registry to donate blood, marrow, and other tissues for regenerative therapy. Issue 3 (10th February 2020) - Liao, Gary; Gilmore, Karen; Steed, Anthony; Elmoazzen, Heidi; Allan, David S.
Abstract : BACKGROUND: As research surrounding cell‐based regenerative therapy advances toward human trials, greater demand for cell products sourced from healthy donors will arise. The extent to which volunteers in Canadian Blood Services Stem Cell Registry would be willing to donate cells to support regenerative therapy is not known and warrants exploration. METHODS: We conducted a Web‐based survey to assess factors that would influence donor willingness to donate various tissues (blood, skin, fat, and bone marrow) for regenerative therapy. The survey was provided to 15, 000 randomly selected donors who registered between 2013 and 2018. Data from the 1118 respondents were analyzed. RESULTS: Despite a mixed degree of familiarity with regenerative medicine, potential donors were very supportive of donating for direct patient care and for research, and increasing their familiarity by reading a brief paragraph of information on regenerative medicine increased willingness to donate. Canadian Blood Servicesʼ stem cell registrants greatly preferred supporting nonprofit groups in research and development in comparison to entities that represent profit‐seeking industry involvement. The most important factors influencing donor willingness to donate were having an impact on patients, safety of donation, advancing knowledge in regenerative medicine, a manageable time commitment, and tolerable pain that could be managed. Donors were most willing to donate blood and had mixed responses to donating other tissue types. CONCLUSIONS: Adult volunteers from a national stem cell registry are willing to support donation of biospecimens for regenerative therapy.